Histologic findings and related diagnostic methods in condylar hyperactivity - Espinosa, Sebastián (2020)
Condylar hyperactivity (CH) is a rare condition that entails a progressive deviation and deformation of the mandible. There is no consensus regarding characteristic histopathological features or a standardized diagnostic process; thus, histopathological analysis of the condyle cannot confirm or exclude an active CH after condylectomy is performed. An electronic search was performed in Medline, Embase, Web of Science, LILACS and grey literature up to December 2019. Additionally, a manual search was performed. Risk of bias of the included studies was assessed using the Newcastle–Ottawa Scale and the Institute of Health Economics Quality Appraisal. All analyses were performed independently and in duplicate. Seventeen articles from 660 were included. Six articles were crosssectional studies and 11 were case series. Almost all the articles (14) described an augmented thickness of the cartilage layer associated with cartilage islands within the subchondral bone in patients affected by CH. Histological findings seem to be mostly related to the age of the sample rather than a characteristic description of CH. No clear association was found between SPECT/scintigram uptake and a specific histological finding. Hence, there is a necessity for the development of specific tools for evaluating and reporting studies where histology is needed for diagnosis confirmation